Suppression of Sheath Blight of Rice with Antagonistic Bacteria - Arif Wibowo (Jurnal Perlindungan Tanaman Indonesia, 2001)
Eleven bacterial isolates were isolated from wet rice field in Wates, Kulon Progo. The result of antagonism test on nutrient agar (NA) showed that only two isolates (WKP-4 and WKP-6) were antagonistic to Rhizoctonia solani. Determination on these two isolates showed that they were belong to the group of fluorescent pseudomonads. In the glass house trial, only WKP-6 suppressed the relative lesion height of sheath blight of rice variety IR 50.